In vitro model systems to investigate bile salt export pump (BSEP) activity and drug interactions: A review. (5th August 2016) - Cheng, Yaofeng; Woolf, Thomas F.; Gan, Jinping; He, Kan
Abstract: The bile salt export pump protein (BSEP), expressed on the canalicular membranes of hepatocytes, is primarily responsible for the biliary excretion of bile salts. The inhibition of BSEP transport activity can lead to an increase in intracellular bile salt levels and liver injury. This review discusses the various in vitro assays currently available for assessing the effect of drugs or other chemical entities to modulate BSEP transport activity. BSEP transporter assays use one of the following platforms: Xenopus laevis oocytes; canalicular membrane vesicles (CMV); BSEP-expressed membrane vesicles; cell lines expressing BSEP; sandwich cultured hepatocytes (SCH); and hepatocytes in suspension. Two of these, BSEP-expressed insect membrane vesicles and sandwich cultured hepatocytes, are the most commonly used assays. BSEP membrane vesicles prepared from transfected insect cells are useful for assessing BSEP inhibition or substrate specificity and exploring mechanisms of BSEP-associated genetic diseases. This model can be applied in a high-throughput format for discovery-drug screening. However, experimental results from use of membrane vesicles may lack physiological relevance and the model does not allow for investigation of in situ metabolism in modulation of BSEP activity. Hepatocyte-based assays that use the SCH format provide results that are generally more physiologically relevant than membrane assays. The SCH model is useful in detailed studies of the biliary excretion of drugs and BSEP inhibition, but due to the complexity of SCH preparation, this model is used primarily for determining biliary clearance and BSEP inhibition in a limited number of compounds. The newly developed hepatocyte in suspension assay avoids many of the complexities of the SCH method. The use of pooled cryopreserved hepatocytes in suspension minimizes genetic variance and individual differences in BSEP activity and also provides the opportunity for higher throughput screening and cross-species comparisons. Highlights: In vitro assays for determining substrate and inhibition of the bile salt export pump (BSEP). Comparison of BSEP membrane vesicle assays with hepatocyte based assays. Applications of BSEP in vitro assays to drug screening paradigms. Use of in vitro BSEP assays for assessing drug interaction potential and drug induced liver injury.